Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1080/09638280801976159
|View full text |Cite
|
Sign up to set email alerts
|

Disability in end-stage knee osteoarthritis

Abstract: Pain, BMI, and antero-posterior laxity of the knee joint were major attributes of self-reported disability. The negative effect of comorbid diseases and female gender on health-related quality of life was significant. The results of objectively measured physical performance tests correlated with self-reported disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 44 publications
5
55
1
Order By: Relevance
“…These findings are consistent with previous research which found moderate to strong (> 0.4) correlations with the WOMAC function and stair climbing, walking or the get-up-and-go test. [319][320][321][322][323] Moderate to strong correlations have also been reported pre-operatively between the WOMAC function and the HHS or its components, 319,321,324 and small to moderate correlations have been found between the WOMAC function and the AKSS. 319,325,326 Our finding of a strong relationship between the Ab-A and WOMAC function score is not surprising as the Ab-A is based on several items of the WOMAC.…”
Section: Discussionmentioning
confidence: 90%
“…These findings are consistent with previous research which found moderate to strong (> 0.4) correlations with the WOMAC function and stair climbing, walking or the get-up-and-go test. [319][320][321][322][323] Moderate to strong correlations have also been reported pre-operatively between the WOMAC function and the HHS or its components, 319,321,324 and small to moderate correlations have been found between the WOMAC function and the AKSS. 319,325,326 Our finding of a strong relationship between the Ab-A and WOMAC function score is not surprising as the Ab-A is based on several items of the WOMAC.…”
Section: Discussionmentioning
confidence: 90%
“…Older age is commonly accepted to be associated with severe disability in knee OA [21]. Obesity has been shown to represent a significant contributor to disability resulting from knee OA [13,21], and higher body weight is associated with slower task performance [10,13]. We thus calculated the mean of each performance-based measure, adjusting for age and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Various relationships between knee OA and indicators of physical performance have been examined, including chair stand, walking, and functional reach. However, those investigations have focused mainly on patients with knee OA, who may have severe symptoms or other underlying conditions [6][7][8][9][10][11]. Findings among patients with knee OA in clinical settings thus may not be extrapolated to individuals living in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Knee osteoarthritis is one of the most prevalent afflictions of the elderly, with patients reporting pain and functional limitations (Kauppila et al, 2009;Laxafoss et al, 2010). Objectively, there is a loss of articular cartilage, visible as a narrowing of the joint space, particularly at the medial side (Hunter et al, 2009), and often accompanied by varus alignment.…”
Section: Introductionmentioning
confidence: 99%